2007
DOI: 10.1055/s-2007-991149
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Prader-Willi Syndrome with Cerebral Venous Thrombosis: Association or Fortuity?

Abstract: A newborn female born at term was admitted at 28 hours for seizures and generalized hypotonia. Cerebral ultrasound showed a right temporal echogenic lesion confirmed on MRI and thought to be secondary to thrombosis of the vein of Labbé. The EEG showed epileptic discharges over the right temporal region. Extensive thrombotic studies revealed a transiently decreased PTT consistent with a prothrombotic state. The hypotonia did not resolve after the acute phase as expected, raising the possibility of another under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This knowledge could also apply to obesity-related genetic disorders such as PWS, possibly at a young age. For example, a newborn female with PWS has been reported in the literature, with neonatal cerebral venous thrombosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge could also apply to obesity-related genetic disorders such as PWS, possibly at a young age. For example, a newborn female with PWS has been reported in the literature, with neonatal cerebral venous thrombosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the occurrence rates of thrombotic events in the PWS population in our study showed an increasing rate over all age cohorts, with the highest occurrence in the 65+ years age cohort. However, thrombosis has been reported as a risk factor in PWS newborns with cerebral venous thrombosis [20]. Additionally, a study by Butler et al [21] suggested that mean C-reactive protein values, indicators of inflammation, were higher in PWS subjects but similar to those seen in the non-PWS obese individuals with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 96%